Sentiment Analysis of the Performance of the Legal System in Indonesia Based on Twitter Comments Using the Naïve Bayes Algorithm - Rasiban Rasiban; Dadang Iskandar Mulyana; Muhammad Joko Umbaran Kharis Bahrudin; Nicola Marthy (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
The development of social media, especially TWITTER, has become one of the main means for people to express opinions and criticism on various issues, including the performance of law in Indonesia. This study aims to analyze public sentiment towards the performance of law based on TWITTER user comments using the Naïve Bayes algorithm. The research data consists of 1004 comments collected from several videos related to legal topics. The analysis process includes the stages of data crawling, pre- processing (text cleaning, normalization, and tokenization), labeling sentiment into positive, negative, and neutral, and testing the Naïve Bayes model. The results show that the Naïve Bayes algorithm is able to classify sentiment with an accuracy level of 93.73%. The distribution of sentiment from 1004 comments shows that the majority of public opinion is (negative/positive/neutral), which indicates that public perception of the performance of law is still (critical/positive). These findings are expected to be input for related parties to understand public opinion and improve the quality of legal performance in Indonesia